The Relationship Between Self-Compassion and Body Dissatisfaction in Second-Year Nursing Students at the Gorontalo Ministry of Health Polytechnic - Lenny Syamsuddin; Rahmawaty Parman; Rizky Towana (Journal of Community Health Provision, 2026)
This study aimed to examine the relationship between self compassion and body dissatisfaction among second year nursing students at the Gorontalo Ministry of Health Polytechnic. The study employed a quantitative correlational design involving nursing students as respondents. Data were collected using a self compassion scale based on Neff’s concept and a body dissatisfaction scale based on Cooper’s framework. The data were analyzed using Pearson correlation analysis with the assistance of SPSS version 26. The findings showed that most respondents had moderate levels of self compassion and moderate levels of body dissatisfaction. The Pearson correlation test indicated a significant negative relationship between self compassion and body dissatisfaction, with a correlation coefficient of r equals negative 0.225 and a significance value of p equals 0.05. This finding suggests that students with higher self compassion tend to experience lower body dissatisfaction, whereas students with lower self compassion are more likely to report higher dissatisfaction with their body image. The study highlights the importance of self compassion as a psychological resource that may help nursing students develop healthier body acceptance and reduce negative evaluations of physical appearance. These findings also imply the need for supportive educational and psychological interventions that strengthen self kindness, common humanity, and mindfulness among students who face body image pressures in academic and social environments.